Empiricism and experience - Gupta, Anil, 1949- (Oxford : Oxford University Press, 2006)
The author asks one of the key questions in philosophy: what is the contribution of experience of knowledge? He uses tools from philosophical logic to show that a natural account of experience is available using the interdependence of views and perceptual judgements.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Experience; Knowledge, Theory of; Empiricism